Reproduksi Sosial dan Dominasi Simbolik Nelayan di Lingkungan Ujung, Kabupaten Polman - M, Ahmad Zaki; Suparman Abdullah; Mansyur Radjab (Universitas Muslim Maros, 2025)
This study investigates the mechanisms of social reproduction and symbolic domination within the patron–client (punggawa–sawi) relationships in the fishing community of Ujung Neighbourhood, focusing on how structural inequality persists through cultural and symbolic processes. The strength and novelty of this research lie in its application of Pierre Bourdieu’s theory of social practice as an analytical lens to move beyond one-dimensional economic explanations, enabling a dialectical understanding between individuals’ subjective experiences and the objective reality of the Ujung environment. Through this perspective, poverty and dependence are not seen as static conditions but as dynamic outcomes of the interaction among habitus, capital, and field in fishermen’s everyday practices. Using a qualitative approach, this study was conducted in Lingkungan Ujung Kabupaten. Data were collected through in-depth interview and participative observation. There are ten informants involved in the study, consisting of three punggawa and seven sawi, who were selected using purposive sampling. They varied in age (between 30 and 60) and education level (between junior high school and S1). The findings reveal that punggawa consolidate multiple forms of capital to maintain authority by: economic capital through boat ownership and market control; social capital through networks with traders and local authorities; cultural capital through maritime knowledge and leadership; and symbolic capital expressed in legitimacy and community respect. These intertwined capitals allow them to extend influence beyond economic relations into social and symbolic realms, normalizing domination as morally justified. Conversely, sawi possess limited capital and inherit a habitus of dependency, reinforcing subordination and limiting mobility. The study concludes that breaking this cycle requires interventions addressing both economic inequality and the sociocultural mechanisms that legitimize and perpetuate domination.